Quasi-homogeneous polynomial differential systems having a center at the origin. (May 2020) - Xiong, Yanqin; Lu, Shiping
Abstract: This paper investigates the quasi-homogeneous polynomial differential systems with a center at the origin. It provides general forms of the corresponding systems and presents two algorithms finding all possible systems with a given degree or a given weight degree by the algebraic analysis method. As an application, two special cases have been studied.